The Polish zloty and currency speculation - Tatiana Fic (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
This paper uses Markov switching models to study short-run movements of the Polish zloty and speculative phenomena in Poland, that is, to investigate whether the exchange rate is "contaminated" by a speculative bubble. The zloty movements are examined in terms of so-called long swings - periods of prevailing appreciation and depreciation of the exchange rate. Speculative fluctuations of the zloty are investigated within two different frameworks: the uncovered interest parity hypothesis and a model of a zloty bubble. The results obtained suggest that the zloty exchange rate is characterised by interweaving periods of appreciation and depreciation with different durations. The uncovered interest parity hypothesis does not hold. Periods were identified, in which the zloty exhibited "bubble properties".
Keywords: C32; F31; 330; Markov switching; exchange rates; speculative bubbles; Wechselkurs; Devisenspekulation; Bubbles; Zinsparität; Schätzung; Markovscher Prozeß; Polen